PENGELOLAAN PENDIDIKAN MENENGAH ATAS PASCA UNDANG-UNDANG PEMERINTAHAN DAERAH - Andi Akbar Herman (Universitas Slamet Riyadi, 2019)
Education is the constitutional right of every citizen, as mandated in the 1945 Constitution of the Republic of Indonesia, so that good management of education will support the progress of a nation. The attraction of government affairs in terms of education carried out by the central government to the district governments to the provincial regions actually further alienated public services. The type of research used in compiling this study is empirical legal research. The results showed that the management of education has implications for the ineffectiveness of the management of senior secondary education in Kolaka Utara district both from the aspect of budget management, management of facilities and infrastructure and management of human resources, no longer effective. This situation has made the provincial government have to establish a branch office in North Kolaka district to support administrative arrangements in the North Kolaka district.